A New Adaptive Prioritization and Fail-Over Mechanism for Ring Network Adapter - Amin Khalilzadegan; Mohammad Zarei; Khayrollah Hadidi (IEEE Access)
This paper presents a new adaptive prioritization and fail-over mechanism for ring network adapters (RNA). Owing to the use of a shared medium in the structure of ring networks, management of network resources is very important and cannot completely be fulfilled by fixed priority strategies. An adaptive prioritization mechanism for efficient utilization of network resources is proposed in this paper. Hop-Count and the distance between source and destination are the key parameters that are included in the priority assignment procedure. Unlike the conventional ones, the arrived traffic is not put blindly into the queues thanks to the awareness of stations form status of each other. The newly introduced fail-over mechanism is based on the Power over Ethernet concept. Each station monitors the heartbeat of its neighbors and tries to keep them alive by providing their minimum required electrical power whenever a fault occurs. By doing so, not only single failure but also any successive double failure scenarios cannot disrupt data path continuity. Several simulations are carried out to assess the behavior and performance of the proposed methods in OPNET Modeler. Moreover, a high-speed USB test board is designed using Xilinx-Spartan6-lx9 FPGA to experimentally verify the performance of the proposed mechanisms.